Hayden White and Conversational Pluralism - Tozzi, María Verónica (2014)
In 1973 Hayden White proposed a theory of historical work through a classification, which not only showed different ways to research and write history, but also explained why these differences are irreducible, and therefore pluralism is inevitable and controversial. The controversial pluralism that Metahistory bequeathed was not well received. It was interpreted, and still is in some sectors, as a celebration of ‘anything goes’ and an ‘attack’ on academic history. In this article I focus on two alternative and critical readings of White’s work, which I call ‘experiential foundationalism’ and ‘metahistorical conceptualism’. While criticizing aspects of these two reading strategies, I propose to reconsider these critical interventions by suggesting a reading of Whitean tropology in combination with figural realism and in the context of a ‘conversational pluralism’ oriented towards the emplotment and reconstruction of past controversies. I conclude by suggesting that to appreciate tropology in terms of a heuristic discipline helps us bring to light irreconcilable differences, but also enables us to refigure in a democratic and dialogic way ‘challenges’ to history arising from public representations of the ‘practical past’.